An analysis of inter-professional collaboration in osteoporosis screening at a primary care level using the D'Amour model - Toh, Li Shean; Lai, P.S.M.; Othman, S.; Wong, K.T.; Low, B.Y.; Anderson, CLaire (Elsevier, 2017)
Objectives